2017
DOI: 10.1007/s11695-017-2967-0
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective 2-Year Follow-up of Late Complications Treated Surgically and Endoscopically After Laparoscopic Roux-en-Y Gastric Bypass (LRYGB) and Laparoscopic Sleeve Gastrectomy (LSG) for Morbid Obesity

Abstract: LRYGB was found to be associated with a greater risk of late complications. If larger databases confirm these results, the trend toward LSG is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…acute pancreatitis which may occur in 9.4%, but also, stenosis, abdominal abscess, pulmonary embolism, deep venous thrombosis may appear. [ 47 , 48 , 50 , 51 ] However, according to the position statement on sleeve gastrectomy as a bariatric procedure by American Society for Metabolic and Bariatric Surgery (ASMBS), LSG is a preferred method of obesity treatment as a first-step management. [ 52 ] In our study the complication rate was 2.5% (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…acute pancreatitis which may occur in 9.4%, but also, stenosis, abdominal abscess, pulmonary embolism, deep venous thrombosis may appear. [ 47 , 48 , 50 , 51 ] However, according to the position statement on sleeve gastrectomy as a bariatric procedure by American Society for Metabolic and Bariatric Surgery (ASMBS), LSG is a preferred method of obesity treatment as a first-step management. [ 52 ] In our study the complication rate was 2.5% (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Lu et al 20 , the risk of fracture in the surgical group, compared with the control group, increased by 1.21 times, with malabsorption procedures presenting a significantly higher risk, with a tendency to increase in the first 1 to 2 years after the procedure. Javanainen et al 17 , in one of the studies with the longest follow-up of patients, also showed a higher risk of fractures in bariatric patients. Corroborating these findings, other observational studies included also found similar results.…”
Section: Global Fracture Riskmentioning
confidence: 93%
“…Among the included studies, 12 were observational studies (10 cohort studies, 1 case-control study, and 1 case series) 5,6,[13][14][15][16][17][18][19][20][21][22] and 3 interventional clinical studies (2 randomized and 1 nonrandomized). [23][24][25] Most of the studies were conducted in the United States, with the majority of participants being premenopausal women.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations